Networks for pervasive services six ways to upgrade the internet - Liotta, Antonio (Lecture Notes in Electrical Engineering, 2011)
Beautifully written, this book takes the reader on a compelling tour of the state of affairs in todays Internet and the challenges it faces for supporting pervasive services of tomorrow. The approach adopted by the authors looks at the big picture, discussing the evolution of the Internet from a rigidly defined layered architecture to an interactive multi-faceted system providing, beyond connectivity, a more generative next-generation network infrastructure. In this context, the authors describe a selection of some of the prominent network mechanisms that may help in shaping the architecture of the future Internet. Overall, this book is informative, enjoyable, and an excellent reference source for every student, network professional, or researcher interested in the post-Internet era. Prof. Raouf Boutaba, University of Waterloo (Canada) Since its inception in the 1970s the Internet has become larger, faster and wireless. It is the biggest machine ever built, the generative engine of our digital society. However, the software that runs the global network has not seen any substantial upgrade since the early 1990s. It is now evident that the existing mechanisms that transport data around the Internet are no longer adequate for the new breed of Web applications. This book explains why the time is ripe for a complete overhaul in view of the Future Internet. Through a series of simple examples, the authors present a wealth of network mechanisms, starting from those that sustain the Web today. Readers will become familiar with a range of advanced protocols that will make the Internet more ubiquitous, reactive, proactive, information-driven, distribution-efficient and searchable.  This book presents a selection of remarkable research ideas, making them accessible to the non-specialist reader.